Synaptic Activity and Muscle Contraction Increases PDK1 and PKCβI Phosphorylation in the Presynaptic Membrane of the Neuromuscular Junction - Hurtado, Erica; Cilleros, Víctor; Just, Laia; Simó, Anna; Nadal, Laura; Tomàs, Marta; Garcia, Neus; Lanuza, Maria A.; Tomàs, Josep (Frontiers in Molecular Neuroscience, 2017)
cPKCβI is a conventional PKC isoform directly involved in the regulation of neurotransmitter release in the neuromuscular junction (NMJ). It is located exclusively at the nerve terminal and both synaptic activity and muscle contraction modulate its protein levels and phosphorylation. cPKCβI molecular maturation includes a series of phosphorylation steps, the first of which is mediated by phosphoinositide-dependent kinase 1 (PDK1). Here, we sought to localize PDK1 in the NMJ and investigate the hypothesis that synaptic activity and muscle contraction regulate in parallel PDK1 and cPKCβI phosphorylation in the membrane fraction. To differentiate the presynaptic and postsynaptic activities, we abolished muscle contraction with µ-conotoxin GIIIB in some experiments before stimulation of the phrenic nerve (1 Hz, 30 min). Then, we analysed total and membrane/cytosol fractions of skeletal muscle by Western blotting. Results showed that PDK1 is located exclusively in the nerve terminal of the NMJ. After nerve stimulation with and without coincident muscle contraction, total PDK1 and phosphorylated PDK1 (pPDK1) protein levels remained unaltered. However, synaptic activity specifically enhanced phosphorylation of PDK1 in the membrane, an important subcellular location for PDK1 function. This increase in pPDK1 coincides with a significant increase in the phosphorylation of its substrate cPKCβI also in the membrane fraction. Moreover, muscle contraction maintains PDK1 and pPDK1 but increases cPKCβI protein levels and its phosphorylation. Thus, even though PDK1 activity is maintained, pcPKCβI levels increase in concordance with total cPKCβI. Together, these results indicate that neuromuscular activity could induce the membrane targeting of phosphorylated PDK1 in the nerve terminal of the NMJ to promote the phosphorylation of the cPKCβI, which is involved in ACh release.